1998
DOI: 10.1034/j.1600-0420.1998.760518.x
|View full text |Cite
|
Sign up to set email alerts
|

Accurate time interval in repeated tonometry

Abstract: The time interval between successive IOP measurements should be 2 or 10 minutes for accurate tonometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 3 publications
(4 reference statements)
0
32
0
1
Order By: Relevance
“…A study demonstrated that successive measurements obtained by applanation tonometry one minute apart showed an almost linear decrease of IOP (Motolko et al 1982), whereas another study found no statistical significance between two measurements performed 10 minutes apart (Recep et al 1998). The second part of the present study indicated the overall IOP trend was not affected by serial measurements of IOP and that episodes of hypertension did not seem to be affected by the repeated measuring of IOP.…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that successive measurements obtained by applanation tonometry one minute apart showed an almost linear decrease of IOP (Motolko et al 1982), whereas another study found no statistical significance between two measurements performed 10 minutes apart (Recep et al 1998). The second part of the present study indicated the overall IOP trend was not affected by serial measurements of IOP and that episodes of hypertension did not seem to be affected by the repeated measuring of IOP.…”
Section: Discussionmentioning
confidence: 99%
“…An interval of at minimum 10 min was given between the utilization of each IOP measurement device to enhance the accuracy of the sequential measurements [9]. The CCT measurements were performed prior to the IOP measurements to avoid the influence of instruments, topical anesthetics and the fluorescein dye on measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The order of the measurements with the two other tonometers (GAT and Schiötz) was randomized. Tonometry measurements were performed approximately 10– 15 min apart, which was shown to be a safe interval for repeated tonometry [10]. …”
Section: Methodsmentioning
confidence: 99%